Diagnosis Concordance in Liaison Psychiatry Patients Transferred From a tertiary Center to Inpatient Psychiatric Care - Tabea Winkler; Nadine Cossette (BJPsych Open)
Aims: A subset of patients assessed by the Liaison Psychiatry service at the Royal Infirmary of Edinburgh are transferred for inpatient psychiatric care. The aim of this audit was to investigate diagnosis concordance, length of stay and nature of follow-up in this cohort. A comparison was made with a previous version of this audit from 2019.